Dynamics of the Global Savanna and Grassland Biomes (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Savanna and grassland biomes cover more of the earth's surface than any other biome type, and yet they are still largely understudied. In recent decades, global savanna and grassland ecosystems have become more prominent in the literature focused on global change dynamics. Savanna and grasslands represent unique biomes with their own challenges, both in terms of their study and in terms of their complexity, leading to many contradictory and often controversial findings. The global threats to these systems are potentially significant, from climate change impacts to human management challenges, from possible degradation to complete desertification, which vary across disturbance regime shifts. This Special Issue of Applied Sciences, “Dynamics of Global Savanna and Grassland Biomes”, is intended for a wide and interdisciplinary audience, and covers recent advances in: - drivers of vegetation dynamics - further understanding carbon interactions in these critical landscapes - advances in modeling both current and future system states - tipping points in savanna systems - human-environment interactions and challenges for management - biodiversity and ecosystem services